Legal Protection of Notaries in Document Validation through Technology-Based Systems: A Comparative Legal Review of Indonesia, the United States, the Netherlands, and Australia - Nazran, Fina; Purba, Hasim; Saidin, O.K.; Kaban, Maria (Journal of Ecohumanism, 2024)
This paper examines the legal framework and challenges notaries face in adopting technology-based systems for document validation in Indonesia, with a comparative analysis involving the United States, the Netherlands, and Australia. Indonesia’s legal framework, particularly Law No. 2 of 2014 on the Office of Notary, has yet to fully accommodate electronic signatures and remote notarization. The requirement for in-person meetings for authenticating notarial acts creates a regulatory barrier to implementing cyber notary services. Furthermore, Indonesian notaries face limited access to essential data systems, such as Dukcapil (Civil Registration Directorate) and BPN (National Land Agency), complicating the verification of personal identity and property documents. In contrast, the United States has adopted e-notary systems, using blockchain technology to ensure data integrity and mitigate fraud risks. The Netherlands provides an integrated platform, allowing notaries to validate documents remotely by accessing national databases in real time. Meanwhile, Australia has implemented a Digital Identity Program to facilitate efficient online authentication of documents. These innovations demonstrate how interoperability, regulatory flexibility, and digital literacy can enhance notary services and legal certainty. This paper proposes regulatory reforms in Indonesia, including revising existing laws to support remote notarization and electronic signatures. Second, developing integrated data platforms for real-time access. Third, providing training programs for notaries to adopt new technologies and ensure data security. By aligning Indonesia’s legal framework with international best practices, cyber notary services can enhance efficiency, security, and legal protection for both notaries and the public, meeting the demands of the digital era.Comparison